2005
DOI: 10.1038/sj.npp.1300939
|View full text |Cite
|
Sign up to set email alerts
|

Personality and the Subjective Effects of Acute Amphetamine in Healthy Volunteers

Abstract: Individual differences in the positive mood and other subjective effects of d-amphetamine have been linked to personality traits related to sensation seeking. The current study extends these associations to separate personality traits of reward sensitivity, physical fearlessness, and impulsivity. A total of 128 healthy volunteers received oral doses of d-amphetamine (10 and 20 mg) or placebo in counterbalanced order. Their responses to the drug were measured using the Profile of Mood States, Addiction Research… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
79
1
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(99 citation statements)
references
References 46 publications
18
79
1
1
Order By: Relevance
“…Participants rated their responses along a 100 mm line ranging from 'none/not at all' (0 mm) to 'a lot/very much'. The sensitivity of the DEQ across different psychoactive substances, including alcohol, has been demonstrated previously (Kirk and de Wit, 2000;White et al, 2005). The BAES is a 14-item adjective rating scale of alcohol's stimulant and sedative effects, with scale items ranging from 0 ('not at all') to 10 ('extremely').…”
Section: Measures Of Subjective Effectsmentioning
confidence: 97%
“…Participants rated their responses along a 100 mm line ranging from 'none/not at all' (0 mm) to 'a lot/very much'. The sensitivity of the DEQ across different psychoactive substances, including alcohol, has been demonstrated previously (Kirk and de Wit, 2000;White et al, 2005). The BAES is a 14-item adjective rating scale of alcohol's stimulant and sedative effects, with scale items ranging from 0 ('not at all') to 10 ('extremely').…”
Section: Measures Of Subjective Effectsmentioning
confidence: 97%
“…One of the most striking examples is 'the telescoping effect', where following initial cocaine use, women meet criteria for abuse/dependence or enter treatment programs after fewer years of drug use as compared with men (Hass and Peters, 2000;McCanceKatz et al, 1999;Griffin et al, 1989;White et al, 2006). This is a robust effect that has been reported not only for cocaine but also for alcohol, heroin, and amphetamine (Anglin et al, 1987;Westermeyer and Boedicker, 2000;Brady and Randall, 1999;Hernandez-Avila et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The personality dimension of novelty or sensation seeking is associated with the initiation of drug use and the frequency and amount of drug use among adolescents and young adults (Brennan et al 1986;White et al 2005;Wills et al 1994Wills et al , 1995. Furthermore, individuals with these personality traits are at increased risk for the development of drug abuse and dependence (Hawkins et al 1992;Huba et al 1981).…”
Section: Introductionmentioning
confidence: 99%
“…Several recent clinical studies suggest that high sensation seekers are also more sensitive to the behavioral effects of stimulants (Hutchison et al 1999;Perkins et al 2000;Sax and Strakowski 1998;White et al 2005). However, not all studies have found a positive association between sensation seeking and sensitivity to stimulant drugs (e.g., Alessi et al 2003;Carrol et al 1982;Chait 1993;Corr and Kumari 2000;de Wit et al 1986).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation